2019
DOI: 10.1002/pssr.201900187
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Silicon Detector for IR Range Coated with Ag2S Quantum Dots

Abstract: For decades, silicon has been the chief technological semiconducting material of modern microelectronics and has a strong influence on all aspects of the society. Applications of Si‐based optoelectronic devices are limited to the visible and near infrared (IR) ranges. For photons with an energy less than 1.12 eV, silicon is almost transparent. The expansion of the Si absorption to shorter wavelengths of the IR range is of considerable interest for optoelectronic applications. By creating impurity states in Si,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…As shown in Figure , a heterojunction was formed between Ag 2 S and silicon. The injection of photogenerated carriers into silicon would significantly improve the durability of the photocatalyst . During four cycle experiments, the heterojunction sample almost remains constant photocatalytic H 2 evolution (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure , a heterojunction was formed between Ag 2 S and silicon. The injection of photogenerated carriers into silicon would significantly improve the durability of the photocatalyst . During four cycle experiments, the heterojunction sample almost remains constant photocatalytic H 2 evolution (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Wavelength-selective ultraviolet (UV) photodetectors (PDs) with high spectral selectivity and narrow full-width at half-maxima (FWHM) are highly desired for wide applications, including flame sensors, selected-wavelength imaging, military, fluorescence detection, UV phototherapy, etc. [1][2][3] Here, light with a specific range of wavelength needs to be detected while the background or environmental radiation needs to be suppressed. [4] For instance, in biophotonics, narrow band detectors are crucial for laser-induced fluorescence detection of hazardous airborne pathogens and discriminating between biological and nonbiological particles in real time.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kang et al synthesized monodisperse Ag 2 S NPs by using a sonochemical method and fabricated photodetector devices by integrating Ag 2 S NPs on a graphene sheet [ 17 ]. Tretyakov et al [ 18 ] reported the characterization of a Ag 2 SQD (quantum dots)/Si heterojunction photodetector used for short-wave infrared radiation fabricated by a chemical method. They show that the Ag 2 S quantum dots (QDs) planted on the surface of Si create impurity states in the Si bandgap.…”
Section: Introductionmentioning
confidence: 99%